Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M161 - Wiebke Mohr; Stefan Kinne; Anne-Cathrin Wölfl (PANGAEA, 2021)
Multibeam bathymetry raw data was recorded in the Atlantic during cruise M161 that took place between 2020-01-17 and 2020-03-03. The data was collected using the ship extquotesingles own Kongsberg EM 122. This data is part of the DAM (German Marine Research Alliance) project Underway Research Data.